When Is a Job Not a Job: Justifications of Part-Time Faculty Work in English and Math Departments at Three Colleges and Universities (Higher Education Politics and Economics, 2025)
This article investigates justifications by academic professionals regarding part-time faculty working conditions, and it is based on sixty-two qualitative interviews in two disciplines at three post-secondary schools. While each university or college had its own justificatory strategy to claim their use of part-time professors was legitimate, each defined part-time faculty work as something other than a real job. The part-time faculty willing to express dissatisfaction regarding their work explicitly want faculty work to be a real job. Finally, the organizational structures of each college reinforce their respective justificatory strategies. This includes three different organizational boundaries between full- and part-time faculty members that can be metaphorically described as a wall, gateway, or ladder. Policy implications are identified regarding the need for pro-rata pay and participation in self-governance.